Procholeragenoid: a safe and effective antigen for oral immunization against experimental cholera. - Pierce, N F (1983)
The immunogenicity and safety of procholeragenoid, a minimally toxic, heat-induced aggregate of cholera toxin (CT), were studied in enterically immunized rats and dogs. Although 99% less toxic than CT, procholeragenoid was only slightly less efficient in causing jejunal anti-CT responses in rats; in contrast, choleragenoid, the nontoxic B subunit pentamer of CT, was much less effective. The immunogenicity of procholeragenoid was due almost entirely to its large-molecular-weight components (MW = 10(6) to 10(7)) and was markedly reduced by preincubation with GM1 ganglioside or treatment with Formalin to eliminate residual toxicity. These findings suggest that molecular aggregation, binding to GM1 receptors on cell membranes, and stimulation of cellular adenylate cyclase each contributed to the effectiveness of procholeragenoid as a mucosal immunogen. In dogs, oral immunization with five 500-micrograms doses of procholeragenoid evoked vigorous anti-CT responses in jejunal mucosa without causing significant diarrhea. When subsequently challenged with virulent Vibrio cholerae, immunized dogs showed 83% protection against the development of severe or lethal diarrhea compared with non-immunized controls. These results confirm a protective role for mucosal antitoxin in experimental cholera and show that procholeragenoid is both safe and effective as an oral immunogen. Procholeragenoid, combined with other antigens of V. cholerae, may constitute a simple, safe, and effective oral vaccine for cholera.